2014
DOI: 10.1680/macr.13.00165
|View full text |Cite
|
Sign up to set email alerts
|

Non-compression X-bracing system using CF anchors for seismic strengthening of RC structures

Abstract: Cross-bracing (X-bracing) is one of the most popular methods of seismic retrofitting. Research results indicate that X-bracing significantly increases structural stiffness and enhances the strength of the structures. However, researchers have also noted that conventional steel X-bracing methods can involve brittle failure at the connection between the brace and the building, as well as buckling failure of the braces. The current research thus investigated the structural properties of a new type of non-compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…as well as buckling-restrained [22,32] and other innovative layouts of steel braces [33][34][35][36][37]. The retrofit hypothesis developed here is based on the adoption of a dissipative bracing system incorporating pressurized fluid viscous (FV) spring-dampers, originally conceived and implemented by the authors for installation in frame buildings [38][39][40].…”
Section: S Sorace G Terenzi Soil Dynamics and Earthquake Engineerimentioning
confidence: 99%
“…as well as buckling-restrained [22,32] and other innovative layouts of steel braces [33][34][35][36][37]. The retrofit hypothesis developed here is based on the adoption of a dissipative bracing system incorporating pressurized fluid viscous (FV) spring-dampers, originally conceived and implemented by the authors for installation in frame buildings [38][39][40].…”
Section: S Sorace G Terenzi Soil Dynamics and Earthquake Engineerimentioning
confidence: 99%
“…Others have analysed the materiality of the braces because conventional steel braces have a buckling failure in some cases. For instance, in [34] the non-compression carbon fibre X-bracing system was analysed. They concluded that this system increases the strength and it has no buckling failure, but this system must be improved, especially in connection with the original structure.…”
Section: Plos Onementioning
confidence: 99%
“…. CF X bracing strengthening system for seismic [17] The externally bonded reinforcement (EBR) is typical strengthening method using FRP as shown in Figure 5. There are a number of researches about externally strengthening of reinforced concrete structures using FRP for flexural and shear, punching shear, extension of fatigue life, strengthening design methodology [14][15][16].…”
Section: Strengthening Technique Of Existing Concrete Structures Usinmentioning
confidence: 99%
“…There are a number of researches about externally strengthening of reinforced concrete structures using FRP for flexural and shear, punching shear, extension of fatigue life, strengthening design methodology [14][15][16]. Recently, carbon fiber X-bracing strengthening system for seismic as shown in Figure 6 was developed and the structural efficiency was experimentally proved under the earthquake loading condition [17]. Above tremendous experimental results were contributed to establish the design and construction specification using FRP in Korea.…”
Section: Strengthening Technique Of Existing Concrete Structures Usinmentioning
confidence: 99%